Analysis of e-wallet application adoption through the diffusion of innovation theory approach (study of e-wallet application users in Bengkulu city) - Muhammad Rizqi Muliadi; Berto Usman (Institute of Computer Science (IOCS), 2024)
This research aims to examine the influence of relative advantage, compatibility, complexity, triability, and observability on the decision to adopt e-wallet applications in Bengkulu City. The object of this research is the people of Bengkulu City who use the e-wallet application. A total of 261 data were collected using a survey with a purposive sampling technique. using non-probability techniques in purposive sampling as a sampling approach. To see the hypothesis results, SmartPLS 4 is used to manage the data. The test results show that relative advantage and compatibility have no effect on adoption decision, while complexity, trialability, and observability have a positive effect on adoption decision